Development of PETA SITAYA Media Based on Deep Learning Integrated with Tri-Nga in IPAS Learning to Improve Elementary Students’ Critical Reasoning - Tri Wulandari; Banun Havifah Cahyo Khosiyono; Ari Setiawan; Ana Fitrotun Nisa (CV. Creative Tugu Pena, 2026)
This study addresses the need for innovative learning media to enhance elementary school students’ critical reasoning skills in IPAS (Ilmu Pengetahuan Alam dan Sosial) learning. The objectives of this research were: (1) to develop a Deep Learning–based educational game media called PETA SITAYA integrated with the Tri-Nga concept; (2) to determine the feasibility of the developed instruments and product; and (3) to examine the effect of the media on improving students’ critical reasoning skills. This study employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The subjects included a limited trial involving 24 students and a wider trial consisting of 29 students in the control class and 29 students in the experimental class. Data were collected through needs analysis questionnaires, expert validation sheets, teacher response questionnaires, and critical reasoning tests in the form of pretest and posttest. The instrument validity test showed 15 valid items (r-count ≥ 0.4044) with a reliability coefficient (Cronbach’s Alpha) of 0.704. Since the data were not normally distributed, nonparametric tests were applied. The Wilcoxon Signed Rank test indicated significant differences between pretest and posttest scores in both classes (Sig. 0.000). The Mann–Whitney U test revealed a significant difference between the experimental and control classes (Sig. 0.000), with the experimental class obtaining a higher mean rank. The findings conclude that the Deep Learning–based PETA SITAYA media integrated with Tri-Nga significantly improves students’ critical reasoning skills in IPAS learning.